Analysis of Implementation Outdoor learning in High School based on Type of School - Tika Mayang Sari; Hifni Septina Carolina (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2019)
This study was aim to know the implementation of outdoor learning at high school level in terms of type of school. This research was a survey research with qualitative descriptive approach. The research was conducted in three types of high schools, namely public schools, adiwiyata schools and integrated Islamic schools based on boarding school. Type of School includes; SMA A as public school, SMA B as adiwiyata school and SMA C as an integrated Islamic school based on boarding school. The sample was obtained by purposive sampling technique consisting of X class biology teacher, class XI and class XII in each school. The research instrument uses an observation note sheet and an interview guide. Analysis of observation and interview data using descriptive qualitative analysis. Documentation data is analyzed using learning tools such as Learning Implementation Plan (RPP) and Student Worksheet (LKS) used by teachers. The results of this study are as follows: (1) The three types of SMA have been implementing outdoor learning (2) Each type of school has the potential to be the object of outdoor learning (3) There are obstacles in the allocation of time in SMA A, the lack of inventory of biology outdoor learning tools in SMA B and no obstacles in SMA C to date (4) SMA B is the most potential school in implementing learning of biology based on outdoor learning.Keywords: Outdoor learning, High schooll, Type of school